2019
DOI: 10.1001/jamapediatrics.2018.4575
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics for Children With Recurrent Abdominal Pain

Abstract: , as well as acknowledging the work of the authors of the original 2009 review. Clinical question: Do dietary interventions, such as probiotics, improve pain in children with recurrent abdominal pain (RAP)? Clinical application: Compared to placebo, children treated with probiotic preparations were more likely to experience improvement in pain in the short term (odds ratio of 1.63, 95% confidence interval 1.07-2.47); suggesting that clinicians could consider probiotics as part of a holistic management strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…109 Probiotic preparations may improve abdominal pain in children in the short term. 114 However, another randomised, double-blind, placebo-controlled trial found that Saccharomyces cerevisiae CNCM I-3856 at a dose of 1 g day À1 does not improve intestinal pain and discomfort in patients with general IBS. 110 A multicentre, randomised, double-blind, placebo-controlled, crossover trial looking at a probiotic mixture of B. infantis M-63, B. breve M-16V, and B. longum BB536 demonstrated improved abdominal pain and quality of life in children with IBS.…”
Section: Probiotics Prebiotics and Synbioticsmentioning
confidence: 99%
“…109 Probiotic preparations may improve abdominal pain in children in the short term. 114 However, another randomised, double-blind, placebo-controlled trial found that Saccharomyces cerevisiae CNCM I-3856 at a dose of 1 g day À1 does not improve intestinal pain and discomfort in patients with general IBS. 110 A multicentre, randomised, double-blind, placebo-controlled, crossover trial looking at a probiotic mixture of B. infantis M-63, B. breve M-16V, and B. longum BB536 demonstrated improved abdominal pain and quality of life in children with IBS.…”
Section: Probiotics Prebiotics and Synbioticsmentioning
confidence: 99%
“…A well-maintained gut microbiota diversity is essential for a normal life, whereas alterations to it (dysbiosis) have impacts on the gut-brain axis, leading to a variety of neurological diseases, such as neuropsychiatric disorders ( Ochoa-Repáraz et al, 2020 ; Ni et al, 2021 ). Gut microbiota alterations are also noticed in patients suffering from different types and areas of chronic pain, including visceral pain, inflammatory pain, headache, neuropathic pain, and chronic widespread pain ( Newlove-Delgado et al, 2019 ; Yang et al, 2019 ; Chen et al, 2020 ; Guida et al, 2020 ; Freidin et al, 2021 ). Based on these studies, we believe that two possibilities should not be neglected: one is that chronic pain may lead to dysbiosis, and the other is that gut microbiota may be a possible way to regulate chronic pain conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the intervention group noted the markedly higher quality of life improvement in comparison with a placebo (48% vs. 17%, p = 0.001) [ 150 ]. A 2009 review by Newlove-Delgado et al retrospectively investigating the use of probiotics in children with recurrent abdominal pain suggested that those preparations are likely to improve pain symptoms in the short term, that is, up to 3 months (OR = 1.63; 95% CI = 1.07–2.47) [ 151 ]. By contrast, a randomized, placebo-controlled trial by Spiller et al failed to identify any clinical benefit, including intestinal pain and discomfort, of S. cerevisiae I-3856 supplementation at a dose of 1000 mg per day, in comparison to a placebo [ 152 ].…”
Section: The Gut Microbiota As a Therapeutic Target In Chronic Painmentioning
confidence: 99%